Pedagogical Resocialization of Children and Youth with Behavioral Problems - Matilda Karamatić Brčić; Ana Marija Iveljić; Iva Serdarević (MDPI AG, 2023)
Deinstitutionalization of care and transformation of homes represent changes and improvement in the Croatian social welfare system's work with children and young people. In the context of the deinstitutionalization processes in this article, we consider the resocialization process of children and youth with behavioral problems, and we are focused on pedagogical resocialization as one of the main prerequisites for its successful operationalization. Therefore, this research subject is considered from the point of view of an interdisciplinary approach. The aim of the qualitative research is to analyze opinions and experiences of educational specialists and educators of the Community-based Service Center in Zadar, by conducting semi-structural interviews about the implementation of the pedagogical resocialization of children and youth with behavioral problems in the above-mentioned institution. According to the obtained results, it is possible to recognize their affirmative attitude towards resocialization processes within the framework of deinstitutionalization, whose implementation they consider as a successful simulation of family life. They also mention some shortcomings within the social welfare system; but, at the same time, the results imply that deinstitutionalization, as a kind of progress within the social welfare system, can also represent an incentive for the progress of all other factors and systems cooperating in this matter, such as the educational system.